“Crime and Punishment” in Greece, 1889-1912 - Šljivančanin, Zorka (Mundo Eslavo, 2017)
Over a period of two decades (1889-1912) two translations of Crime and Punishment were published in Greece. The first version of the work was translated by one of the most eminent prose writers of the period, Alexandros Papadiamantis, and appeared in serial form in the first mass circulation daily Athenian newspaper Efimeris (from April 14 until August 1, 1889). The second Greek edition was translated by Stelios Haritakis and published in Crete in 1912. Both translations were rendered from the first French edition of Crime and Punishment translated by Victor Derely (1884). The article explores the early translational reception of Dostoevsky’s novel in Greece. It focuses on the Epilogue and aims to analyze the translation of the words that are closely related to the two basic motives of the work: the motive of crime and the motive of regeneration. In addition, some of the questions that will be considered are: what is missing in the French and Greek editions of the Epilogue and what are the consequences of these omissions? Which phrases/words were added to the two Greek versions and why? Can we talk about creative translation in the case of the first Greek edition of Crime and Punishment, taking into account that the translator was a writer himself?